Silver nanoparticles as antimicrobials: A comparative analysis of green and traditional chemistry synthesis methods - Karla Vizuete; Dayanna Gabriela Cabascango; Tamia Xaymara Iza García; António Machado; Fernanda Pilaquinga; Lenys Fernandez; Patricio J. Espinoza-Montero; Alexis Debut (PLoS ONE, 2026)
Silver nanoparticles (AgNPs) have garnered attention due to their antimicrobial properties and applications in nanomaterials. The objective of this study is to compare the antimicrobial activities of AgNPs synthesized using green and traditional methods with silver ions (Ag + ). The characterization of AgNPs was conducted through the utilization of UV-Vis spectroscopy, energy-dispersive X-ray spectrometry, transmission electron microscopy, X-ray diffraction, and differential pulse voltammetry (DPV). AgNPs presented quasi-spherical nature and well-dispersed characteristics, with a mean diameter around 10nm and 25nm for the traditional and green methods respectively. DPV measurements showed a decline of the area under the curve from 1.79 μA mm -2 to 0.7679 μA mm -2 , indicating limited colloidal stability of green AgNPs. In contrast, traditional AgNPs demonstrated stability over time, maintaining an area under the curve of around 31 μA mm -2 over a 30-day period. The antimicrobial efficacy against Staphylococcus aureus and Escherichia coli was assessed via the broth dilution method. The results indicated that there were similar minimum inhibitory concentrations and minimal bactericidal concentrations (MIC and MBC) for both nanoparticle types and Ag + against S. aureus (≈ 1 mM). While differences were detected against E. coli : traditional AgNPs evidenced lower MIC and MBC values on day 30 (≈ 0.5 mM) and Ag + evidenced MIC and MBC values of 0.5 and 0.75 mM on both days 1 and 30. Green AgNPs exhibited heightened antimicrobial activity over time, as evidenced by the planktonic growth of S. aureus and E. coli in days 1 and 30. This observation is concomitant with an increase in Ag⁺ release evidenced by DPV, underscoring the key role of silver ions in mediating antibacterial effects. This research contributes to a more comprehensive understanding of how synthesis method, nanoparticle stability, silver ion release, and testing methodology influence the antimicrobial performance of AgNPs, offering insights critical for their practical application.